THE IMPACTS OF SOCIAL MEDIA ON THE YOUTH’S INTERPERSONAL COMMUNICATION - Maharsi Widya Astuti; RINY JEFRI; Lely Novia (Ikatan Dosen Katolik Indonesia, 2023)
The purpose of this study was to find out whether or not the use of social media by youth decreases social interaction with friends. This study used a quantitative method using a simple random sampling technique to take the sample. The subjects of this study were Business English Communication students from batches 2019, 2020, and 2021. This study has two variables, namely social media (X) and interaction with friends (Y). A questionnaire was used as the method for collecting data for this study. Two types of questionnaires: open-ended and closed-ended questionnaires, were used as the instruments and data collection techniques. Data analysis employed the normality test, linearity test, and t-test for testing hypotheses. Based on the questionnaire results, data analysis was conducted, and the results for the two variables ell into the high category. The t-test results showed that when the value of t-count exceeds t-table (7.722> 2.002), H0 is rejected. Thus, it can be said that the findings are consistent with the Alternative Hypothesis, which contends that youth use of social media decreases friend interaction.